ENGLISH LANGUAGE LEARNING: A SURVEY OF MOTIVATION AND PREFERRED ACTIVITIES AMONG ENGINEERING STUDENTS IN POLYTECHNIC KUCHING SARAWAK - Mohd Redzuan, Nor Syahidzan; Buda, Agnes; Abdullah, Nur Syafiqa Aqiera (Journal of Techno-Social, 2013)
Language learning is influenced by various factors determined by learners or educators. Motivation is one of the many factors that had sparked the interest of many educationists as it is known to give impact to the learning process and the performance of the students. In line with that, this research was carried out to find out the types of motivation (instrumental and integrative) and the preferred language activities among engineering students. A total sample of 100 students from four engineering departments in Polytechnic Kuching Sarawak, namely Electrical Engineering Department, Mechanical Engineering Department, Petrochemical Engineering and Civil Engineering Department were selected randomly. The distributed questionnaires consists of two main parts; types of motivation and language activities. ‘Statistical Package for Social Sciences’ (SPSS) was applied to analyze the feedback obtained. The findings had shown that most of the students are instrumentally motivated in learning English. Majority of the students responded that they learn English in order to pass the course of their study and increase their future career opportunities. Interactive activities such as problem-based activities and role playing are preferred by the students in learning English.